Long-term evolution of postpartum sacroiliac bone marrow oedema: a 5-year longitudinal follow-up study - Varkas, Gaëlle; De Meester, Liesbet; de Hooge, Manouk; De Craemer, Ann-Sophie; Herregods, Nele; Jans, Lennart; Carron, Philippe; Elewaut, Dirk; Van den Bosch, Filip (Rheumatic & musculoskeletal diseases open, 2025)
IntroductionBone marrow oedema (BME) on MRI of the sacroiliac joints (SIJ) commonly occurs after pregnancy. Our goal was to assess the evolution of BME over a period of 5 years and the potential development of structural lesions.MethodsMRI-SIJ was performed after an uncomplicated vaginal delivery, with a follow-up 5 years later, evaluating both inflammatory and structural lesions.Results19 women were assessed. Mean age was 35.3 years, with median body mass index of 20.8. Six subjects reported back pain, of which only one reported inflammatory back pain (IBP). No association was found between IBP and Spondyloarthritis Research Consortium of Canada (SPARCC) score (p=0.24), nor with a positive MRI according to the Assessment of SpondyloArthritis international Society (ASAS) definition at baseline (p=0.64). Thirty-two percent (6/19) presented with BME after 5 years, 3 of whom met the ASAS definition of a positive MRI-SIJ, irrespective of subsequent pregnancies. A new delivery during follow-up was linked to the total number of structural lesions at year 5, whereas mean weight gain across all pregnancies correlated with sclerosis. Sclerosis and erosions were more frequently detected by synthetic CT compared with T1-weighted MRI.ConclusionsIn postpartum women, no significant development of structural MRI lesions was observed 5 years after a single delivery, despite the presence of BME in a significant number of individuals postpartum and at follow-up. These results support the hypothesis that, unlike BME in SpA, childbirth-related mechanical stress-induced BME does not lead to structural lesions. However, subsequent pregnancies may contribute to their development.